REGULATORY DOCUMENTS IN TERRITORIAL AND URBAN PLANNINGIN BULGARIA – HISTORY AND CONTEMPORARY - KOVACHEV, ATANAS; ENCHEV, NIKOLAI (E-Journal VFU, 2024)
Bulgaria ranks among the countries with a developed regulatory system in the field of territorial planning, town planning and architecture. The regulatory framework in urban planning has a dynamic nature and determines the quantitative requirements for meeting the various needs of the 414 population by types of objects and activities. The expected result of this article is the formulation of a proposal for a new normative regulation of the territorial organization, which more accurately reflects the reality of the necessary change to more effective territorial-organizational planning. In connection with this, a systematic analysis has been made and conclusions have been drawn that substantiate the prerequisites and trends for the possible subsequent changes in the legislative normative regulation of the territorial organization. An article is a prerequisite for provoking a debate among the collegium of architects, urban planners and legislators.